Penatalaksanaan Nyeri pada Tindakan Bedah Mulut - Teguh Iman Santoso (Faculty of Dentistry, Universitas Indonesia, 2015)
It is well known that almost all of dental treatment in dentistry especially in oral surgery associated with pain. It is make uncomfortable feeling and fear for the patient. It's responsibility for the dentist to know the patofisiology of pain and how to relief it. Recently, beyond knowledge and technology in dentistry and pharmacology, there are many drugs to relief of pain, especially from derived NSAID. For selecting analgesic drugs, accurately or effective and minimal side effect, perhaps we must know the biotransformation of NSAID. Generally, NSAID drugs it choose who works specific in COX-2 inhibitor and work minimized in COX-1.